Factors Related to Pregnancy Incidents in Adolescents at Mebung Primary Healthcare Center Working Area, Alor Regency - Malaikosa, Lianna Melina; Riwu, Yuliana Radja; Landi, Soleman (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: The number of teenage (less than 20 years old) pregnancies at Mebung Primary Healthcare Center working area increased every year from 2020 to 2023. In 2020, there were 28 cases of pregnancy; increased to 30 cases in 2021 and 40 cases in 2022 until 50 cases in 2023. Thi study aimed to determine the factors of teenage pregnancies at Mebung Primary Healthcare Center, Alor Regency working area.Methods: This quantitative study used a cross-sectional study design. The dependent variable was teenage pregnancy, while the independent variables were knowledge, attitudes, exposure to information, the role of parents, and the role of peers. The population in this study was 565 adolescents at Mebung Primary Healthcare Center working area. The subjects were 65 female adolescents, which was chosen through simple random sampling method. Data analysis were done through chi-square tests, with a significance level of 95% (α=0.05).Results: There was a significant association between knowledge (p=0.0001), attitude (p= 0.0001), exposure to information (p=0.0001), the role of parents (p= 0.006), the role of peers (p=0.0001) with the incidence of pregnancy in adolescents at Mebung Primary Healthcare Center working area.Conclusion: Lack of knowledge, attitude, information exposure, parents’ support, peers’ support could lead to a higher incidence of teenager’s pregnancy at Mebung Primary Healthcare Center working area.